Reduced and Compressed Cisplatin-Based Chemotherapy in Children and Adolescents With Intermediate-Risk Extracranial Malignant Germ Cell Tumors: A Report From the Children’s Oncology Group - Shaikh, Furqan (J Clin Oncol, 2017)
PURPOSE: To investigate whether event-free survival (EFS) can be maintained among children and adolescents with intermediate-risk (IR) malignant germ cell tumors (MGCT) if the administration of cisplatin, etoposide, and bleomycin (PEb) is reduced from four to three cycles and compressed from 5 to 3 days per cycle. PATIENTS AND METHODS: In a phase 3, single-arm trial, patients with IR MGCT (stage II-IV testicular, II-III ovarian, I-II extragonadal, or stage I gonadal tumors with subsequent recurrence) received three cycles of PEb. A parametric comparator model specified that the observed EFS rate should not be significantly < 92%. As recommended for trials that test a reduction of therapy, a one-sided P value ≤ .10 was used to indicate statistical significance. In a post hoc analysis, we also compared results to the EFS rate of comparable patients treated with four cycles of PEb in two prior studies. RESULTS: Among 210 eligible patients enrolled from 2003 to 2011, 4-year EFS (EFS(4)) rate was 89% (95% confidence interval, 83% to 92%), which was significantly lower than the 92% threshold of the comparison model (P = .08). Among 181 newly diagnosed patients, the EFS(4) rate was 87%, compared with 92% for 92 comparable children in the historical cohort (P = .15). The EFS(4) rate was significantly associated with stage (stage I, 100%; stage II, 92%; stage III, 85%; and stage IV, 54%; P < .001). CONCLUSION: The EFS rate for children with IR MGCT observed after three cycles of PEb was less than that of a prespecified parametric model, particularly for patients with higher-stage tumors. These data do not support a reduction in the number of cycles of PEb from four to three. However, further investigation of a reduction in the number of cycles for patients with lower-stage tumors is warranted.